The patterns and variations of the circle of willis and their relationship with cerebral aneurysm using ct angiography in hospital universiti sains malaysia: a radio anatomical study - Mossa, Abubakr H (2012)
The complete arterial circle of Willis provides collateral circulation by its communicating arteries to meet the high cerebral metabolic demand. However, many studies showed that the complete circle of Willis is atypical in about 40 -70% of population. The reason behind this was due to the relatively common occurrence of anomalies in the cerebral vessels. The atypical circles showed higher incidence of cerebral vascular diseases like aneurysm and cerebral infarction. Nowadays, advancements in imaging studies, like computed tomography (CT) angiography, made it easier to study the cerebral vessels and their anomalies with high level of accuracy. This imaging modality is widely used to detect cerebral vascular diseases in the Hospital Universiti Sains Malaysia (HUSM) and the database is available and easily accessible. The database can be considered as a rich source for anatomical studies. So the main objective of this study was to identify the different patterns of circle of Willis in the patients underwent CT angiography in HUSM and the relationship between these patterns and the development of aneurysms. This was done by examining the brain CT angiographies retrospectively by recording the diameters of the vascular segments. Anomalies and aneurysm sites were recorded. Upon that the sample was divided into two groups; group with aneurysm and another group without aneurysms. Then the different patterns were identified and statistical tests were used to compare my findings with other populations and to relate these anomalies with aneurysms development. The study showed that aneurysms were found in 55% of the (123) patients with significant higher incidence in females and in older age (p < 0.05). Gender and side differences in vessels diameters were not proven and the anomalies were detected significantly more in the posterior communicating artery. The aneurysm group showed higher incidence of anomalies as well (p< 0.001). Overall, the complete pattern was represented in only 17% but significant difference in the occurrence of incomplete circles in aneurysm group was not detected. Conclusions inferred as that the vessels diameters, anomalies prevalence and aneurysm sites in this population were comparable to others. The presence of vascular anomalies could be related to aneurysms development especially by noticing the relationship between the higher prevalence of anomalies in the posterior segments of the circle of Willis and the higher prevalence of aneurysms in the anterior vascular segments. Finally, the incomplete pattern in the studied population was higher than other population which reflected the total sample as it was derived from diseased cases.